The Role of Knowledge Sharing in Organizational Performance - Al Kashari, Zainab; Al Taheri, Fatma (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
With the tremendous development in the current world, it has become necessary for organizations to convey with the rhythm of development in order to achieve the advantage of constructive competition with other organizations in their field. Where knowledge management is considered one of the methods used to raise the level of development, increase revenue and competitive advantage. The purpose of this paper is to discover the role of knowledge sharing in the organization in terms of increasing the effectiveness and efficiency, the significance of knowledge sharing, relationship between knowledge sharing and organizational leadership, the issues of knowledge sharing and how can be addressed. The applied method in this study is Qualitative Research which includes the use of non-statistical data to explain or explore a certain phenomenon. This paper has been failed to include the correspondence between knowledge sharing, employee motivation and performance, as this topic is also reflective of the extended role of knowledge sharing in the efficiency, satisfaction and retention of employees.